Nodal and cripto-1: distinct functions regulate trophoblast specification in mouse pregnancy - Girardet, Laura; Kamath, Neha; Dufort, Daniel (Frontiers in Cell and Developmental Biology, 2025)
IntroductionProper placentation is essential for fetal growth and development in mammals. Nodal signaling is essential to ensure proper embryo development and requires Cripto-1 as a co-receptor. Both factors have been shown to be expressed in the maternal decidua and developing placenta. Notably, a maternal loss of either Nodal or Cripto-1 leads to defective placentation resulting in intrauterine growth restriction and fetal loss. However, the role of Nodal or Cripto-1 in placental development has not been determined.MethodsTo better understand the roles of Nodal and Cripto-1 in trophoblast populations, we employed a trophoblast-specific deletion model using Tat-Cre recombinant protein to induce deletion of the floxed Nodal or Cripto-1 genes exclusively in the trophectoderm at the blastocyst stage (TE-KO). Treated embryos were then transferred into the uteri of pseudopregnant mice, and implantation sites were examined at gestational days (d) 8.5 and 10.5. Placental morphology and trophoblast populations were analyzed through histological and molecular marker analysis.ResultsTE-KO of Nodal led to a decrease in the implantation site size and placental thickness, primarily due to a smaller labyrinth area while the junctional zone was increased. Immunostaining revealed an important expansion of PL+ trophoblast giant cells and decrease of TPBPA+ spongiotrophoblast/glycogen cells. TE-KO of Cripto-1 also led to smaller implantation sites and reduced placental thickness, but this was attributed to a smaller junctional zone. A decrease in TPBPA+ spongiotrophoblast cells without affecting Pcdh12+ glycogen cells was observed. A reduction in MCT1+ and Gcm1+ syncytiotrophoblasts and an increase in total area of maternal blood sinuses within the labyrinth emphasized its disorganization. Earlier effects of Cripto-1 TE-KO on the trophoblast maintenance were witnessed at d8.5, with a marked reduction in TPBPA+ cells, reduced trophoblast cell proliferation (PCNA+) and increased apoptosis (TUNEL+).DiscussionThe distinct phenotypes observed indicate the different roles Nodal and Cripto-1 play in placental development. This highlights the importance of other TGF-β-dependent and independent pathways involving Cripto-1. Overall, our findings highlight the critical role of Nodal and Cripto-1 in regulating key aspects of placental development, including trophoblast differentiation, cellular specification, and structural organization, promising avenues for future research in placental biology.